Mathematical model, validation and analysis of the drying treatment on quality attributes of chicory root cubes considering variable properties and shrinkage - Balzarini, Maria Florencia (2018)
This work presents an exhaustive three dimensional mathematical model to describe chicory root cubes drying process (Cichorium intybus L.) using a Fick's diffusion model considering a variable diffusion path length in three dimensions. Experimental data obtained at laboratory scale is used to validate the proposed model. Experiments are conducted using a forced convection laboratory dryer at temperatures of 60 °C and 80 °C and air velocities of 0.2 and 0.7 m/s to dry chicory root cubes of 1 cm of side. Mathematical modeling is firstly used to represent the performance of the drying process with the temporal variations of the average humidity content, to determine diffusion coefficients, and afterwards, to obtain useful predictions on how the volumetric contraction of the cubes behaves under different operating conditions. The good agreements between experimental and predicted values prove that the proposed model can be applied to the precise description of experimental drying curves for chicory roots in three dimensions (3-D). In the ranges covered, the values of the effective moisture diffusivity were obtained between 5.63 × 10−5 and 8.21 × 10−5 cm2/s. Results from the analysis of rehydration and browning aspects illustrate that drying conditions have effects on the quality attributes of the dried samples.